FLASH early science – discovery of an intervening H i 21-cm absorber from an ASKAP survey of the GAMA 23 field. Issue 3 (9th April 2020) - Allison, J R; Sadler, E M; Bellstedt, S; Davies, L J M; Driver, S P; Ellison, S L; Huynh, M; Kapińska, A D; Mahony, E K; Moss, V A; Robotham, A S G; Whiting, M T; et al.
ABSTRACT: We present early science results from the First Large Absorption Survey in H i (FLASH), a spectroscopically blind survey for 21-cm absorption lines in cold hydrogen (H i ) gas at cosmological distances using the Australian Square Kilometre Array Pathfinder (ASKAP). We have searched for H i absorption towards 1253 radio sources in the GAMA 23 field, covering redshifts between z = 0.34 and 0.79 over a sky area of approximately 50 deg 2 . In a purely blind search, we did not obtain any detections of 21-cm absorbers above our reliability threshold. Assuming a fiducial value for the H i spin temperature of T spin = 100 K and source covering fraction c f = 1, the total comoving absorption path-length sensitive to all Damped Lyman α Absorbers (DLAs; N H i ≥ 2 × 10 20 cm −2 ) is Δ X = 6.6 ± 0.3 (Δ z = 3.7 ± 0.2) and super-DLAs ( N H i ≥ 2 × 10 21 cm −2 ) is Δ X = 111 ± 6 (Δ z = 63 ± 3). We estimate upper limits on the H i column density frequency distribution function that are consistent with measurements from prior surveys for redshifted optical DLAs, and nearby 21-cm emission and absorption. By cross-matching our sample of radio sources with optical spectroscopic identifications of galaxies in the GAMA 23 field, we were able to detect 21-cm absorption at z = 0.3562 towards NVSS J224500−343030, with a column density of N_H I = (1.2 ± 0.1) × 10^20 (T_spin/100 K) cm −2 . The absorber is associated with GAMA J22450.05−343031.7, a massive early-type galaxy at an impact parameter of 17 kpc with respect to the radio source and which may contain a massive ( M H i ≳ 3 × 10 9 M⊙ ) gas disc. Such gas-rich early types are rare, but have been detected in the nearby Universe.